2019
DOI: 10.17224/energagric.2019v34n01p18-27
|View full text |Cite
|
Sign up to set email alerts
|

Emergência E Desenvolvimento De Plântulas De Maracujá-Amarelo Em Diferentes Substratos

Abstract: EMERGÊNCIA E DESENVOLVIMENTO DE PLÂNTULAS DE MARACUJÁ-AMARELO EM DIFERENTES SUBSTRATOS   LAÍS GERTRUDES FONTANA SILVA1; RAMON AMARO DE SALES2; FRANCIELE PEREIRA ROSSINI3; YAGO TONINI DA VITÓRIA1 E SÁVIO DA SILVA BERILLI1   1Instituto Federal do Espirito Santo – Campus Itapina, BR 259, KM 70, Colatina-ES, Brasil, laiisfontana@gmail.com; yago.agro@hotmail.com; berilli@gmail.com 2Departamento de Fitotecnia, Universidade Federal de Viçosa, Avenida Peter Henry Rolfs, s/n, Campus Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The constant production of solid waste generated by industries has become the primary source of pollution worldwide. Silva et al (2019) suggested that if not properly disposed of, solid waste can cause severe damage to the environment. According to the authors, one of the possible solutions would be the reutilization of solid waste, for example, as an alternative substrate, generating savings and, above all, improvements for the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The constant production of solid waste generated by industries has become the primary source of pollution worldwide. Silva et al (2019) suggested that if not properly disposed of, solid waste can cause severe damage to the environment. According to the authors, one of the possible solutions would be the reutilization of solid waste, for example, as an alternative substrate, generating savings and, above all, improvements for the environment.…”
Section: Introductionmentioning
confidence: 99%